Compass for civilization - Gregg,Richard B. (Ahmedabad, 1956)
This book is an attempt to find such a pattern of meaning. Though much of it is culled from the insights of sensitive and wise people of many cultures and many epochs, it is not an anthology. It is an arrangement of such insights related to modern thought, and for me anyhow, the arrangement itself adds meaning and value to the details. So this is a statement of a philosophy of life, a pattern of many wisdoms. But it is not a mosaic of disconnected experiences, nor an Esperanto of faiths nor asyncretism of beliefs.
Keywords: Civilization